Fluorescence studies on new potential antitumoral benzothienopyran-1-ones in solution and in lipid membranes - Castanheira, Elisabete M. S. (2009)
This work was funded by Foundation for Science and Technology (FCT, Portugal) and FEDER through CFUM and CQ-UM, research project PTDC/QUI/81238/2006 and PhD grants of M.S.D. Carvalho SFRH/BD/47052/2008 and of R.C. Calhelha SFRH/BD/29274/2006.